Ginsenoside Rg1 as a promising adjuvant agent for enhancing the anti-cancer functions of granulocytes inhibited by noradrenaline - Zhu, Yuqian; Chen, Jingyao; Li, Jun; Zhou, Chenqi; Huang, Xin; Chen, Bingdi (Frontiers in Immunology, 2023)
In recent years, numerous studies have confirmed that chronic stress is closely related to the development of cancer. Our previous research showed that high levels of stress hormones secreted in the body during chronic stress could inhibit the cancer-killing activity of granulocytes, which could further promote the development of cancer. Therefore, reversing the immunosuppressive effect of stress hormones on granulocytes is an urgent problem in clinical cancer treatment. Here, we selected noradrenaline (NA) as a representative stress hormone. After screening many traditional Chinese herbal medicine active ingredients, a promising compound, ginsenoside Rg1, attracted our attention. We verified the immunoprotective effect of ginsenoside Rg1 on granulocytes in vitro and ex vivo, and attempted to understand its potential immunoprotective mechanism. We confirmed the immunoprotective effect of ginsenoside Rg1 on granulocytes using cell and animal experiments. Cell counting kit-8 (CCK-8) and ex vivo experiments were performed to investigate the immunoprotective effects of ginsenoside Rg1 on the anti-cancer function of granulocytes inhibited by NA. Transcriptome sequencing analysis and qRT-PCR showed that NA elevated the mRNA expression of ARG2, MMP1, S100A4, and RAPSN in granulocytes, thereby reducing the anti-cancer function of granulocytes. In contrast, ginsenoside Rg1 downregulated the mRNA expression of ARG2, MMP1, S100A4, and RAPSN, and upregulated the mRNA expression of LAMC2, DSC2, KRT6A, and FOSB, thereby enhancing the anti-cancer function of granulocytes inhibited by NA. Transwell cell migration experiments were performed to verify that ginsenoside Rg1 significantly enhanced the migration capability of granulocytes inhibited by NA. Tumor-bearing model mice were used to verify the significant immunoprotective effects in vivo. Finally, CCK-8 and hematoxylin and eosin staining experiments indicated that ginsenoside Rg1 exhibited high biosafety in vitro and in vivo. In future clinical treatments, ginsenoside Rg1 may be used as an adjuvant agent for cancer treatment to alleviate chronic stress-induced adverse events in cancer patients.